Metal and pesticide residues levels accumulated in leafy vegetables and several fragrant medicinal plants in Baghdad Governorate / Iraq (Texas Journal of Medical Science, 2023)
The levels of some heavy metals (cadmium, lead, chromium) and pesticide residues (Malathion, Dimethoate, Profernofoes, PrimiohosMe) were estimated in some aromatic medicinal plants (chamomile, anise seeds, coriander, fennel) and leafy vegetables (cabbage, celery, grape leaves, and coriander, Mint, lettuce, spinach, and watercress) are commonly used and collected frm various markets. Organophosphorus pesticides have also been detected in some aromatic medicinal plants and leafy vegetables. Where, chamomile samples showed only Malathion, while in coriander malathion is 0.86 and Dimethoate have been detected in Anise seeds, profernofoes in chamomile were predominant, and leafy vegetables have also been detected some Organophosphorus pesticides in green mint Malathion, profernofoes is dominant, the findings showed that some heavy metals were present in some of the samples that were collected. Lead and chromium levels, as well as varying amounts of cadmium and chromium, were found in grape leaves in the majority of the samples that were examined. Samples of chamomile flowers had the greatest average amounts of cadmium and chromium, whereas samples of anise seeds had the highest levels of lead.